Identification and Characterization of Novel Intracellular α-Xylosidase in Aspergillus oryzae - Matsuzawa, Tomohiko; Nakamichi, Yusuke; Shimada, Naoki (Journal of applied glycoscience : JAG, 2023)
α-Xylosidase releases xylopyranosyl side chains from xyloglucan oligosaccharides and is vital for xyloglucan degradation. Previously, we identified and characterized two α-xylosidases, intracellular AxyA and extracellular AxyB, in Aspergillus oryzae. In this study, we identified a third α-xylosidase, termed AxyC, in A. oryzae. These three A. oryzae α-xylosidases belong to the glycoside hydrolase family 31, but there are clear differences in substrate specificity. Both AxyA and AxyB showed much higher hydrolytic activity toward isoprimeverose (α-D-xylopyranosyl-1,6-glucose) than p-nitrophenyl α-D-xylopyranoside. In contrast, the specific activity of AxyC toward the p-nitrophenyl substrate was approximately 950-fold higher than that toward isoprimeverose. Our study revealed that there are multiple α-xylosidases with different substrate specificities in A. oryzae.